Evaluation and comparison of biomarkers in decompensated heart failure in a tertiary care center - Fathima Nilofar; Gnanadeepan T.; Mahendra Kumar K.; Nitesh Babu R. (Romanian Medical Journal)
Objective. This research delves into decompensated heart failure (DHF), aiming to comprehensively evaluate and compare biomarkers within a tertiary care center. Recognizing DHF's clinical challenges and high morbidity and mortality rates, the study seeks to enhance understanding and shed light on underlying mechanisms, particularly the role of biomarkers. Methodology. Utilizing a retrospective cohort design, the study spans electronic health records from 2010 to 2022. Ethical considerations, including IRB approval and informed consent, are paramount. Biomarkers such as cardiac troponins, B-type natriuretic peptide (BNP), and C-reactive protein (CRP) undergo rigorous assessment via advanced laboratory techniques. Statistical analyses, encompassing t-tests and ANOVA, provide a robust foundation for discerning patterns and correlations. This study includes 200 patients diagnosed with DHF (experimental group) and 200 control patients without DHF (control group). Results. Baseline characteristics highlight subtle differences between DHF patients (experimental group) and controls. Biomarker analysis reveals statistically significant elevations in cardiac troponins, BNP, and CRP in DHF cases compared to controls. The mean levels in survivors and non-survivors underscore the potential prognostic value of these biomarkers. ANOVA results suggest no significant differences in age, gender distribution, and BMI between the groups, reinforcing the robustness of the findings. Conclusion. This study significantly contributes to DHF management insights, emphasizing the diagnostic and prognostic potential of biomarkers. The observed disparities in biomarker levels, coupled with consistent baseline characteristics, provide valuable insights for clinical considerations and future research in DHF management. The nuanced interpretation of results not only expands knowledge of DHF but also offers actionable insights for clinicians dealing with this complex condition. The study's comprehensive approach, combining clinical, demographic, and biomarker data, lays a strong foundation for future investigations and interventions in DHF.